Sistem Informasi Manajemen Kesiswaan (SIMKES) di Lembaga Pendidikan - Sugeng Riyadi; Fariz Ramadan (PT. Hasba Edukasi Mandiri, 2025)
The Student Management Information System (SIMKES) is an information technology-based system designed to assist educational institutions in managing student data and activities more efficiently, accurately, and in an integrated manner. SIMKES includes essential features such as student data recording, attendance management, academic progress monitoring, reporting of violations and achievements, as well as integration with parent or guardian reporting systems. The system aims to replace manual processes that are time-consuming and prone to errors, while also improving transparency and the quality of administrative services in education. This study adopts a software engineering approach using the waterfall model, consisting of requirement analysis, system design, implementation, and evaluation stages. The testing results show that SIMKES enhances the performance of school administrative staff, facilitates teachers in student monitoring, and provides fast data access for school leaders to support strategic decision-making. Moreover, its online reporting feature allows parents to actively monitor their child’s development. SIMKES plays a crucial role in the digital transformation of the education sector, supporting the creation of a modern, efficient, and responsive administrative system that meets current demands.